Pengaruh Gambler’s Fallacy, Halo Effect, Familiarity Effect Terhadap Pengambilan Keputusan Investasi Pada Investor Milenial Di Kota Semarang - Nabyan, M Balan; Yusuf, Muhammad (Magister Manajemen STIE Bank BPD Jateng, 2025)
In the current era, technology is increasingly developing in providing facilities especially in public services. Withthe advancement of technology, the stock exchange is developing in the younger generation, especially in CentralJava. In the last 5 years the Central of Java has increased every year, especially in the city of Semarang whichhas the highest increase in young investors from Central Java. This study aims to determine the effect of gambler’sfallacy, halo effect, familiarity effect on investment decision making on millennial investors. The population in thisstudy were all young investors in the city of Semarang. The sample is determined using the purposive samplingmethod and the number of samples chosen is 100 samples. The analytical tool in this study is multiple linearregression. The results show that gambler’s fallacy, halo effect, familiarity effect influences significant effect oninvestment decision making. Behavioral gambler’s fallacy, and familiarity effect bias are potentially grater thanthat in halo effect. The contribution of this study provides empirical evidence that the behavior of bias gambler’sfallacy, halo effect, familiarity effect affects investment decision making for millennial investors.